Identity-based earning discrimination among Chinese people - Abu Bakkar Siddique (IZA Journal of Development and Migration, 2020)
Hukou registration is an instrument to control nonplanned population and capital movements, which the Chinese Communist Party has been exploiting extensively since the 1950s. It requires that each Chinese citizen be classified as either an agricultural or nonagricultural hukou inheritor and be distinguished by their location with respect to an administrative unit. Hukou distribution used to be entirely determined by birth, but nowadays, Chinese citizens can self-select their hukou status based on their ability that causes selection bias in conventional wage decomposition by hukou types. To avoid this bias, I estimated hukou-based earning discrimination by matching Chinese individuals based on a rich set of individual-, family-, and society-level characteristics. By deploying a recent nationally representative dataset, this paper finds that significant earning discriminations exist against agricultural hukou people. I further investigated the impact of hukou adoption within work ownership, work and employer types, and labor contract conditions. I argue that earning difference by hukou is not due to rural-urban segregations; rather, it is systematic and institutionally enforced. This is because, contrary to self-employment and no labor contract conditions, discrimination exists only when others employ them and where a labor contract condition is enforced. Moreover, they face discrimination only when they work for the Chinese government, not when they work for private firms, and they face higher discrimination in nonagriculture-related professions compared to agriculture-related professions.
Keywords: C21; C31; I38; J7; J71; J15; J31; N35; 330; Hukou; labor market; earning discrimination; development; migration; matching estimator; China